British’s Bush On The Iberian Peninsula: Analisis Sekuritisasi Inggris Terhadap Sovereignty & Dilema Keanggotaan Schengen Gibraltar Pasca-Brexit - Adriesa, Aura Azzahra; Wiswayana, Wishnu Mahendra (Journal of Integrative International Relations, 2025)
This study examines the securitization strategy advanced by the UK government concerning Gibraltar’s sovereignty and its fraught relationship with Schengen membership in the post-Brexit period. The research focuses on border control methods and official statements and how Gibraltarians react to these measures as their main point of object referent. The research establishes new knowledge through its investigation of speech acts and public opinions and its evaluation of state actions which convert border matters into national security threats. The research uses qualitative case-study methodology to analyze secondary documents which include official statements and legislative instruments such as the Protocol on Gibraltar and related agreements and media reports and discourse analysis. The research reveals three connected systems which work together to achieve their goals: (1) Speech acts serve to validate British control over UK Overseas Territory; (2) Gibraltarians support British sovereignty yet they want to maintain their European freedom of movement; (3) The UK implements three exceptional border control systems which combine military patrols with dual identification checks and special border procedures to defend their sovereignty while creating more travel obstacles. The research establishes a direct link between political statements and actual border changes and institutional developments which shows that securitization like used as function to maintain current sovereignty structures (status quo) instead of creating lasting solutions for border movement. The research results include vital policy recommendations which impact multilevel negotiations that occur on the Iberian Peninsula